The role of the vestibular system in value attribution to positive and negative reinforcers. (December 2020) - Blini, Elvio; Tilikete, Caroline; Chelazzi, Leonardo; Farnè, Alessandro; Hadj-Bouziane, Fadila
Abstract: Somatic inputs originating from bioregulatory processes can guide cognition and behavior. One such bodily signal, mostly overlooked so far, is represented by visuo-vestibular coupling and its alteration, which in extreme cases may result in motion sickness. We argued that the inherently perturbed interoceptive state that follows can be a powerful determinant of human motivated behavior, resulting in a blunted response to appetitive stimuli and an exaggerated response to noxious ones. We sought to assess such differential impact of visuo-vestibular mismatches on value through a task involving conflict monitoring. We therefore administered to 42 healthy participants a modified version of the Flankers task, in which distractors (arrows, pointing in either a congruent or incongruent direction) signaled the availability of monetary incentives (gains, losses, or neutral trials). While performing the task, participants received either galvanic vestibular stimulation (GVS), or sham stimulation. We have found impaired behavioral performances when value, which was attached to task-irrelevant information, was at stake. Gains and losses, interestingly, dissociated, and only the latter caused enhanced interference costs in the task, suggesting that negative incentives may be more effective in capturing human attention than positive ones. Finally, we have found some weak evidence for GVS to further increase the processing of losses, as suggested by even larger interference costs in this condition. Results were, however, overall ambiguous, and suggest that much more research is needed to better understand the link between the vestibular system and motivation.